Предикативні та комунікативно-прагматичні особливості гіпотаксису в сучасному англомовному медичному дискурсі - Олексієнко, Алла Валеріївна; Oleksiienko, А. V. (Дрогобицький державний педагогічний університет імені Івана Франка, 2018)
Статтю присвячено дослідженню синтаксичних особливостей англомовного гіпотаксису у фахових медичних текстах. Визначено специфіку предикативності складнопідрядних речень в медичному дискурсі. Також розглянуто синтаксичні конструкції приєднання, парантези та протиставлення англомовного гіпотаксису в комунікативно-прагматичному аспекті. The article is devoted to the study of syntactical features of hypotaxis in English scientific medical discourse. Firstly, the author highlights the necessity of complex linguistic study of professional i.e. institutional communication in medicine. The author informs that special scientific significance takes on the syntax of institutional discourse, and not only the formal-structural aspect of it but also its functional and communicative specificity. It is observed that complex sentence in medical texts is characterized by the specifics of scientific texts, namely, with the maximum information within the same sentence. Then the author describes the predicative organization of hypotaxis as it is its key constitutive feature because it correlates the reported information with reality, and thusforms a unit that is called a statement. It is stated that the predicative organization of complex sentences in medical texts is subjected to their main function, namely, the presentation of objective factual information, therefore the indicative in the present prevails. The characteristic feature is the active use of passive constructions and modal verbs in order to distance from the reader and give certain recommendations. On the communicative-pragmatic level the active use ofsyntactic constructions of adjunction, parentheses and contradiction is used to express the addition of information to the main sentence. As a specific kind of adjunction the author describes determinative clauses that distribute the main sentence in general. As conclusion the author says that not only the level of the complex sentence, but also the comparative analysis ofhypotaxis withparataxis is interestingfor the 'wide study ofmedical discourse.
Predicative and communicative-pragmatic features of hypotaxis in modern English medical discourse
Keywords: медичний дискурс; гіпотаксис; предикативність; приєднання; парантеза; протиставлення; medical discourse; hypotaxis; predication; adjunction; parenthesis; contradiction